2012
DOI: 10.1111/j.1600-0412.2012.01504.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble urokinase plasminogen activator receptor (suPAR) in early pregnancy prior to clinical onset of preeclampsia

Abstract: Objective. To examine whether soluble urokinase plasminogen activator receptor (suPAR) in early pregnancy could be a risk marker for later development of preeclampsia. Design. Case‐control study. Setting. Hospital‐based. Population. The study comprised 43 pregnant women developing preeclampsia (cases) and 86 pregnant women not developing the disorder (controls). Each case was matched with two controls with respect to pre‐pregnancy body mass index, gestational age at time of blood collection, storage time of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Changes in plasmatic haptoglobin have been proposed as a biomarker of preeclampsia [ 5 7 ]. The soluble urokinase plasminogen activating receptor (suPAR) is a newly characterized inflammatory marker during pregnancy, but thus far, no clear evidence of its predictive value for the later development of pregnancy complications has been found [ 8 , 9 ]. Inflammatory changes during pregnancy are accompanied by shifts in gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in plasmatic haptoglobin have been proposed as a biomarker of preeclampsia [ 5 7 ]. The soluble urokinase plasminogen activating receptor (suPAR) is a newly characterized inflammatory marker during pregnancy, but thus far, no clear evidence of its predictive value for the later development of pregnancy complications has been found [ 8 , 9 ]. Inflammatory changes during pregnancy are accompanied by shifts in gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have demonstrated that although long-term storage and repeated freeze-thaw cycles can affect the stability of IL-6, IL-8, IL-10, IFN- γ , and TNF- α , this effect can be attenuated by storing samples at −80°C (32 34). Serum samples of TNFRSF1A, TNFRSF1B, and suPAR have been shown to be resistant to significant degradation after long-term storage and undergoing at least one freeze-thaw cycle (32,35,36). Similarly, levels of serum cystatin C stored for multiple years at −70°C have been shown to remain stable after one freeze-thaw cycle (37).…”
Section: Discussionmentioning
confidence: 99%
“…Since serum suPAR levels are considered to represent the degree of inflammation [14], the significant difference noted in serum suPAR levels between PE and NP indicates that the activation of the inflammatory process is more pronounced in PE and furthermore that suPAR may serve as a potential marker of this inflammatory response [23]. In studies involving patients in the first and early second trimester before the clinical signs of PE are present, the assessment of suPAR concentrations was not found to predict the development of PE in late pregnancy [24,25]. This finding could imply that the inflammatory process in PE is not more pronounced until clinical signs of PE.…”
Section: Discussionmentioning
confidence: 99%